2016
DOI: 10.7759/cureus.883
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Target Cancellation Task to Identify Eloquent Visuospatial Regions in Awake Craniotomies: Technical Note

Abstract: The success of awake craniotomies relies on the patient’s performance of function-specific tasks that are simple, quick, and reproducible. Intraoperative identification of visuospatial function through cortical and subcortical mapping has utilized a variety of intraoperative tests, each with its own benefits and drawbacks. In light of this, we developed a simple software program that aids in preventing neglect by simulating a target-cancellation task on a portable electronic device. In this report, we describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…One possible explanation for this dissociation is that the line bisection task draws on allocentric representation, whereas the core deficit in spatial neglect is egocentric [51][52][53]. Another allocentric test, the target cancelation task, which involves searching for and crossing out target symbols, is more sensitive than the line bisection task for USN detection, but less widely used during AC [16]. For evaluations of social cognition, facial emotion recognition tasks are frequently performed during AC, based on photographs of individuals displaying one of the six primary facial emotions (anger, happiness, fear, surprise, disgust and sadness) extracted from several tests (Ekman's Faces, the Brief Affect Recognition Test, the Japanese and Caucasian Brief Affective Recognition Test, and the ATR facial expression database) [18,54,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this dissociation is that the line bisection task draws on allocentric representation, whereas the core deficit in spatial neglect is egocentric [51][52][53]. Another allocentric test, the target cancelation task, which involves searching for and crossing out target symbols, is more sensitive than the line bisection task for USN detection, but less widely used during AC [16]. For evaluations of social cognition, facial emotion recognition tasks are frequently performed during AC, based on photographs of individuals displaying one of the six primary facial emotions (anger, happiness, fear, surprise, disgust and sadness) extracted from several tests (Ekman's Faces, the Brief Affect Recognition Test, the Japanese and Caucasian Brief Affective Recognition Test, and the ATR facial expression database) [18,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Far fewer procedures have been published for the mapping of optic radiation and visuospatial and social cognition than for language and motor mapping [14,[16][17][18][19][20][21][22][23][24][25][26][27][28]. This may be explained by the complexity of the corresponding functional anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…The other five studies that were deemed unsuitable did assess the functionality of subcortical pathways in executive functions or visuospatial awareness, but did not clearly indicate which subcortical pathway was stimulated and were therefore not considered suitable to answer the research questions of this review. All five unsuitable studies reported on inhibitory control and used the line bisection task [18,59,74,75] or target cancellation task [18] to assess visuospatial awareness or an intraoperative Stroop test to assess inhibition of automatic responses 44 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Cases of right-hemispheric lesions are often operated upon under general anesthesia, based on the perceived low risk of permanent neurological sequelae, with a focus on monitoring motor functions. Despite the importance of right hemisphere functions, there is a paucity of literature on the use of cortical and subcortical mapping on the right hemisphere compared to linguistic mapping in the left hemisphere [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. This lack of interest may stem not only from the underestimation of the right hemisphere’s contribution to cognitive function but also from the intricacies of functional anatomy and the challenges involved in using traditional bedside tasks in awake-surgical situations.…”
Section: Introductionmentioning
confidence: 99%